1993
DOI: 10.1136/hrt.69.3.268
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary artery dissection in a patient with idiopathic dilatation of the pulmonary artery: a rare cause of sudden cardiac death.

Abstract: A 31 year old man presented with a left hilar mass. Thoracic tomography showed this mass to be the pulmonary artery, and subsequently idiopathic dilatation of the pulmonary artery was diagnosed. He remained well until 11 years later when he died suddenly. Postmortem examination confirmed idiopathic dilatation of the pulmonary artery with death due to pulmonary artery dissection and cardiac tamponade.It seems likely that idiopathic dilatation of the pulmonary artery predisposed to fatal pulmonary artery dissect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 9 publications
0
13
0
1
Order By: Relevance
“…Pulmonary artery dissection is a very unusual event. As far as we could ascertain from a Medline survey of the English literature, only 50 cases have been recorded 1–27 . According to Shilkin et al, 2 the first case of the condition was reported by Helmbrecht in 1842.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary artery dissection is a very unusual event. As far as we could ascertain from a Medline survey of the English literature, only 50 cases have been recorded 1–27 . According to Shilkin et al, 2 the first case of the condition was reported by Helmbrecht in 1842.…”
Section: Discussionmentioning
confidence: 99%
“…Entre os 5 casos rotulados como patoló-gicos, 2 com miocardiopatia dilatada e 1 com Insuficiência mitral certamente devem ser acompanhados. Os 2 casos de dilatação idiopática do tronco pulmonar podem ser considerados benignos, porém, relato recente de complicação a longo prazo 19 , questiona a benignidade desse achado. A técnica inadequada na realização do exame assim como a análise incorreta do possível aumento de câmaras foram os motivos que resultaram no encaminhamento da criança.…”
Section: Discussionunclassified
“…Whether medial degeneration causes the dissection, predisposes to intimal tears, or is simply the result of chronically elevated intravascular pressure remains controversial. 47 Approximately 70 cases of PAD have been described, [43][44][45][46][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] of which almost 10 were diagnosed during life. 43,[65][66][67][68][69] Congenital heart disease was the underlying condition in the majority of cases, with the patent ductus arteriosus representing the most common defect.…”
Section: Pulmonary Artery Dissection and Rupturementioning
confidence: 99%